2019
DOI: 10.14414/jebav.v22i1.1589
|View full text |Cite
|
Sign up to set email alerts
|

The long-run and short-run impacts of investment, export, money supply, and inflation on economic growth in Indonesia

Abstract: The development of investment and exports in Indonesia shows an increase, as well as money supply, while the inflation rate shows a decline, but this is not always followed by increasing economic growth. This study aims to explain the relationship between investment, export, money supply and inflation with the economic growth in Indonesia. The data used was time series data from the first quarter in 2001 to the fourth quarter in 2014 and was analyzed using multiple regression models with Error Correction Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…Shahbaz et al [37] confirmed the validity of the ELG hypothesis, both in the short run and the long run, for Pakistan. Kurniasih [38] derived a similar finding for Indonesia. Liang and Zuradi [39] found a positive long-run relationship between export and economic growth for Malaysia, and [40] found supporting evidence for the case of Vietnam.…”
Section: The Export-led Growth Hypothesis and Its Empirical Supportsupporting
confidence: 63%
“…Shahbaz et al [37] confirmed the validity of the ELG hypothesis, both in the short run and the long run, for Pakistan. Kurniasih [38] derived a similar finding for Indonesia. Liang and Zuradi [39] found a positive long-run relationship between export and economic growth for Malaysia, and [40] found supporting evidence for the case of Vietnam.…”
Section: The Export-led Growth Hypothesis and Its Empirical Supportsupporting
confidence: 63%
“…However, if the communities do not demand the loans as expected, the expansionary monetary policy will not assist the growth rates (Kaplan, 2017). As per Kurniasih (2019), a positive relationship has been examined between the rate of interest and the money supply. Hence, when the expansionary monetary policy efforts are taken in relation to the selected contexts of the study, it could be identified that the interest rates are increased in the economies making the people motivated to take less loans.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…In a study for Indonesia, Kurniasih (2019) tested the effect of money supply on economic growth along with exports, investment and inflation in Indonesia. He applied regression technique as well as error correction mechanism to examine effect of stated factors on economic growth.…”
Section: Literature Review 21 Real Money Balances and Outputmentioning
confidence: 99%
“…In economics, the Cobb-Douglas production function is widely used to represent the relationship of an output to inputs. Following the framework established by Sinai and Stokes (1972) for the US economy and studies in context of developing countries like Khan and Ahmad (1985) and Kurniasih (2019) in their estimation of real money balances in the production process to trigger out the influence of money balances on output. Likewise, closely following the studies carried out such as Feridun, Olusi, and Folorunso (2006); Kilicarslan and Dumrul (2018); Maqbool-ur-Rahman (2015) and Ali et al (2020) who determined effect of globalization on economic growth along with labor and capital; this study incorporated real money balances and globalization in production function.…”
Section: Theoretical Frameworkmentioning
confidence: 99%